LEADERSHIP, WORK ATTITUDES, AND MOTIVATION ON EMPLOYEE PERFORMANCE: A QUANTITATIVE STUDY IN THE KUNINGAN REGENCY EDUCATION AND CULTURE OFFICE - Tita Rosita; Ellin Herlina (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study — This research is to determine and examine the influence of leadership, work attitudes, motivation on employee performance.Research method—This research is a quantitative study with regression. This study uses a quantitative approach to see the causal relationship of several factors that influence employee performance. The population in this study were the Kuningan Regency Education and Culture Office employees, totaling 61 employees. Data was collected by questionnaire and document study, after which the data was tested for validity and reliability.Result— The results of the study show that Leadership, Work Attitude and Motivation affect Employee Performance simultaneously. The coefficient of multiple determination in this study uses the adjusted R square value because the independent variables in this study are more than 2 in estimating the effect of the two independent variables studied. From the data the adjusted R Square value is 0.511, this means that together the influence of the variables X1, X2, and X3 is 51.1% on changes in Y or in other words the influence of the independent variables (Leadership, Work Attitude and Motivation) on the dependent variable ( performance) of 51.1% while the remaining 47.9% is caused by other variables that are not included in the research framework.Conclusion— Even though there is an effect, it is still within moderate limits, meaning that the influence is still normal, and this should need improvement in terms of leadership in motivating employees which must be increased again and of course the problem regarding the work attitude of the employees because it is important which will ultimately improve employee performance Kuningan District Education Office.